Analysis of the Influence of Brand Experience on Smartphone Customer Loyalty in Indonesia - Indah Dwi Cahyani; Aldilla Nadhira Ayu Setyaning (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
This research analyzes the influence of brand experience, perceived quality, brand trust, and brand loyalty on smartphone consumers in Indonesia. This research was motivated by the intense competition in the Indonesian smartphone market, so it is important to understand the factors influencing consumer loyalty to brands. This research used a quantitative approach with the Structural Equation Model (SEM) method and data collection through purposive sampling. Data samples were taken from Indonesian smartphone consumers aged 20 to 34, with 280 respondents. This research has five hypotheses, and four of them are accepted. However, perceived quality does not positively and significantly affect brand loyalty.